8th World One Health Congress - a reflection by ILRI scientist Hung Nguyen-Viet - International Livestock Research Institute (International Livestock Research Institute, 2024)
Hung Nguyen is the Leader (a.i.) of Health Program at the International Livestock Research Institute (ILRI) and the leader of the CGIAR initiative on One Health. The focus of the World One Health Congress 2024 held in Cape Town, South Africa on 20–23 September 2024 was on improving human health by taking a holistic approach that considers the interconnectedness of human, animal and environment health.